Science experiments you can eat - Cobb, Vicki, 1938- (Harper Trophy, 1994)
"Experiments with food demonstrate various scientific principles and produce an eatable result. Includes fruit drinks, grape jelly, muffins, chop suey, yogurt, and junket."--Resumé vydavatele
Keywords: kuchařství; příprava jídel; pokusy; věda; vědecké pokusy; cookery; meals preparation; experiments; science; scientific experiments; publikace pro mládež; juvenile literature